STRUCTURAL AND OPTICAL PROPERTIES OF RARE EARTH DOPED PHOSPHATE GLASS CONTAINING NANOPARTICLES - M. R. Sahar; E. S. Sazali; Raja J. Amjad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Transparent rare earth doped phosphate based glasses with and without silver nanoparticles (NPs) are obtained using conventional melt-quenching technique. In the present study, structural properties of glass are investigated by using X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). In addition, the optical properties of glass are investigated by means of UV-Vis-NIRand Photoluminescence (PL).The amorphous nature of the glass is confirmed by XRD diffractogram.TEM studies revealed the nano-crystals glass morphology which is associated to the existence of crystallized phase.It is found that the growth of particle size of silver in glass matrix depends mainly on the diffusion coefficient and activation energy of coalescence and more specifically on the heat treatment time and temperature of the matrix. For UV-Vis-NIR studies, the absorption spectra of RE doped phosphate with NPs presents several sharpabsorption bands due to the respective transitions of RE ionswhich has been transit from the ground state tothe excited states. With the addition of NPs, the wavelengthsof the absorption peaks are almost unchanged but the cut-offabsorption bands shift to shorter wavelengths.The emission peaks for the luminescence were found to be located at the wavelength which corresponding to each rare earth. The enhancement of RE luminescence is due to the presence of NPs. The large luminescence enhancement was obtained due to the simultaneous contribution of the REenergy transfer. Our findings may provide some useful information towards the development of functional glasses with controlled optical properties. Keywords: Rare earth (RE), Nanoparticles (NPs).